Hemodynamic CAE design of blood-wetted medical devices used in treatment of cardiovascular disease - Rojas-Solorzano, L.; Saliev, T.; Adair, D.; Finol, E. (Nazarbayev University, 2013)
Cardiovascular Disease (CVD) leads to the major number of deaths in the USA and Europe (European Heart Network, 2008; US National Center for Health Statistics, 2012). In Kazakhstan, CVD represents also the first cause of fatalities (WHO, 2011) with 346.6 per 100.000 of population by 2011, ranking Kazakhstan in 5th place in the world. Despite the best action to reduce CVD being a lifestyle change, medicine and surgical/non-surgical treatment is also needed for severe cases. This project is partnered with the Center of Life Sciences (CLS), a center of excellence at Nazarbayev University created to ¨transform medicine and healthcare in Kazakhstan through innovative scientific research and rapid translation of breakthrough discoveries.
Keywords: first research week; Cardiovascular Disease; healthcare; health problems; innovative scientific research